The Effectiveness of Role Play in Improving EFL Students' Speaking Ability: A Systematic Literature Review (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to systematically examine empirical evidence on the effectiveness of role play in improving EFL students' speaking skills. Using Systematic Literature Review (SLR) methodology guided by the PRISMA framework, this study analyzed 20 peer-reviewed articles obtained from Google Scholar, ERIC, and Scopus databases. Inclusion criteria focused on studies investigating role play as an instructional technique targeting speaking skills in EFL or ESL contexts. Findings reveal that role play consistently and significantly improves key speaking components including fluency, accuracy, pronunciation, vocabulary, and confidence. Additionally, role play reduces speaking anxiety and promotes a more communicative and interactive learning environment. This review also identifies moderating factors such as class size, student proficiency level, and teacher facilitation quality that influence role play effectiveness. These findings suggest that role play is a highly effective pedagogical strategy for improving speaking competence, particularly in EFL contexts, and its systematic integration into curriculum design is strongly recommended.